2003
DOI: 10.1002/ijc.11079
|View full text |Cite
|
Sign up to set email alerts
|

Plasma DNA microsatellite panel as sensitive and tumor‐specific marker in lung cancer patients

Abstract: The majority of lung cancer patients have tumor-derived genetic alterations in circulating plasma DNA that could be exploited as a diagnostic tool. We used fluorescent microsatellite analysis to detect alterations in plasma and tumor DNA in 34 patients who underwent bronchoscopy for lung cancer, including 11 small cell lung cancer (SCLC) and 23 nonsmall cell lung cancer (NSCLC) (12 adenocarcinomas, 11 squamous cell carcinomas) and 20 controls. Allelotyping was performed with a selected panel of 12 microsatelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
2
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 39 publications
(72 reference statements)
6
53
2
4
Order By: Relevance
“…Whether the elevated concentrations of circulating DNA in cancer patients have the same origin or derive from another source of cells, for example the tumour itself, need further investigation. Qualitative studies have shown that genetic alternations such as mutations and LOH were detected in circulating DNA, as well as in the matching tumour cells, suggesting that part of the extra circulating DNA in cancer patients is attributed to DNA released from tumour cells (Gonzalez et al, 2000;Shaw et al, 2000;Beau-Faller et al, 2003). However, our results indicate that the mechanisms of DNA released from tumours are not related to any of the known commonly used major prognostic factors and therefore might highlight different pathways, such as apoptosis, necrosis, hypoxia, that would need to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the elevated concentrations of circulating DNA in cancer patients have the same origin or derive from another source of cells, for example the tumour itself, need further investigation. Qualitative studies have shown that genetic alternations such as mutations and LOH were detected in circulating DNA, as well as in the matching tumour cells, suggesting that part of the extra circulating DNA in cancer patients is attributed to DNA released from tumour cells (Gonzalez et al, 2000;Shaw et al, 2000;Beau-Faller et al, 2003). However, our results indicate that the mechanisms of DNA released from tumours are not related to any of the known commonly used major prognostic factors and therefore might highlight different pathways, such as apoptosis, necrosis, hypoxia, that would need to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…This finding contradicts previous studies and challenges the utility of this test as a diagnostic tool for lung cancer. Some studies have used healthy blood donor controls, 19 and others have used hospital controls, 15 but most have found no genetic alterations in the plasma DNA of patients without cancer. Our controls are unusual in representing the respiratory clinic population from which the lung cancer patients were derived.…”
Section: Discussionmentioning
confidence: 99%
“…The demonstration that tumour DNA can be detected in the plasma of cancer patients has led to interest in the study of genetic changes in plasma DNA as diagnostic and prognostic markers for several tumour types, including breast, pancreas, colorectal and lung cancers. 5,15 In preliminary studies of plasma DNA in lung cancer, chromosomal deletions, microsatellite alterations and abnormal promoter methylation of tumour suppressor genes have been examined. 16 -18 This has led to the hope that lung cancer might be detected or its prognosis defined using a simple blood test.…”
Section: Abstract: Biomarkers; Diagnosis; Screeningmentioning
confidence: 99%
“…На сегодняшний день много работ посвящено изучению микросателлитных перестроек в цирДНК крови [107][108][109][110][111][112][113]. Микросателлиты -короткие повторяющиеся и высокополиморфные последовательности, состоящие из многократно повторяющегося мотива, например, ди-, три-, тетрануклеотида: (NN-N)n. Микросателлиты более или менее случайно распределены в геноме [114].…”
Section: особенности строения внеклеточных днк кровиunclassified
“…Биологическая функция микросателлитов неясна, однако они часто используются в качестве генетических маркеров для анализа расположения генов-супрессоров опухолей и т.д. Опухолеассоциированные нарушения микросателлитной ДНК были обнаружены в цирДНК плазмы крови при раке лёгких [107], головы и шеи [108], почки [109], мочевого пузыря [110], предстательной железы [111,112] и гепатоцеллюлярной карциноме [113].…”
Section: особенности строения внеклеточных днк кровиunclassified